2011
DOI: 10.1590/s1984-70332011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic gains for heat tolerance in potato in three cycles of recurrent selection

Abstract: -Practically all potato cultivars grown in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 17 publications
(21 reference statements)
1
26
0
3
Order By: Relevance
“…The ideal temperatures for potato cultivation are between 15 and 21 ºC (Haverkort and Verhagen 2008). The effects of high temperatures have been reported in several works carried out in the south of the state of Minas Gerais (Menezes et al 2001, Benites and Pinto 2011, Figueiredo et al 2015. In the present study, the control CBM 16-16 stood out probably due to its tolerance to heat (Menezes et al 2001).…”
Section: Agronomic Performancesupporting
confidence: 52%
“…The ideal temperatures for potato cultivation are between 15 and 21 ºC (Haverkort and Verhagen 2008). The effects of high temperatures have been reported in several works carried out in the south of the state of Minas Gerais (Menezes et al 2001, Benites and Pinto 2011, Figueiredo et al 2015. In the present study, the control CBM 16-16 stood out probably due to its tolerance to heat (Menezes et al 2001).…”
Section: Agronomic Performancesupporting
confidence: 52%
“…Greater than ideal temperatures bring about multiple physiological, biochemical, and molecular processes of the potato plant (Hancock et al 2013). Thus, heat stress delays tuber development, reduces production and dry matter content of the tubers, increases respiration and the partitioning of photoassimilates to the plant shoots (Levy and Veilleux 2007), negatively affects the qualitative appearance of the tubers (Ginzberg et al 2009), and increases the rate of physiological disorders (Benites and Pinto 2011). Thus, studies that seek to obtain heat tolerant potato clones should be a priority in Brazilian breeding programs, and efforts have been made in this direction (Benites and Pinto 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible to conclude that the genotypic variance observed in the last recurrent selection cycle, for both traits, represents the possibility of selection gains in the next cycles. For autogamous species (Menezes Júnior et al, 2008;Breseghello et al, 2009;Niu et al, 2010;Benites & Pinto, 2011;Morais Júnior et al, 2015), recurrent selection has shown good results both for high-and lowheritability traits. Long-term genetic gains in recurrent selection are a result of the continuous increase in the frequency of favorable alleles in the population, pointing the average values of the population to the desired direction.…”
Section: Resultsmentioning
confidence: 99%